The Identification of Multiple Intelligence in Relation to English Achievement of the Sixth Graders of SD Negeri 32 Palembang - Saputri, Kurnia (Institut Agama Islam Negeri (IAIN) Curup, 2018)
The Identification of Multiple Intelligence in relation to English Achievement of the sixth graders of SD N 32 Palembang. Based on the data analysis, there were five major findings: First, linguistic, logical, spatial, musical, and interpersonal intelligences were types of intelligence of the sixth graders. Second, most of the students dominantly have interpersonal intelligence. Third, based on the calculation of z scores (standard scores), Logical-Ma thematical intelligence was the type of intelligence that had better English achievement because this type had the positive scores higher than the negative scores. Fourth, the variance of population was homogeneous. Fifth, the mean value of population was homogeneous and correlated each other.